PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS AURORA 3 DIMENSION (3D) PRESENTATION PADA POKOK BAHASAN HIDROKARBON UNTUK KELAS XI MIA SMA/MA - Wanda Ika Wahyuni Ika Wahyuni; Elva Yasmi Amran Yasmi Amran; Herdini Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Hydrocarbons concepts that are abstract need a learning media to visualize the concepts of hydrocarbons with more concrete. The development of computer technology to encourage the development of computer-based learning media, but only 20-25% are considered valid for the purposes of learning. This research aims to develop chemistry learning media based on Aurora 3D Presentation in hydrocarbons. Development of learning media is one attempt to generate computer based learning media to produce an appropiate and preciss of properness condition media. This type of research is research and development (R & D) with model ADDIE (analysis, design, development, implementation, Evaluation). Collect data is done by using instrument validation sheet, filling by 3 validators. Data obtained in the form of advice and the value of the validation sheet. The average value obtained from the validation is 3.64 for the fourth assessment aspects (design, pedagogic, content, and technical) and 3.67 for the general assessment of the media with valid category. Based on the results of the validation and data analysis can be concluded that hydrocarbons learning media based on Aurora 3D Presentation the Aurora have been valid and can be used in Senior High School.Keywords : Learning Media, Aurora 3D Presentation, Hydrocarbons